Production of single cell protein from agro-waste using Rhodococcus opacus. (1st September 2018) - Mahan, Kristina M; Le, Rosemary K; Wells, Tyrone; Anderson, Seth; Yuan, Joshua S; Stoklosa, Ryan J; Bhalla, Aditya; Hodge, David B; Ragauskas, Arthur J
Abstract: Livestock and fish farming are rapidly growing industries facing the simultaneous pressure of increasing production demands and limited protein required to produce feed. Bacteria that can convert low-value non-food waste streams into singe cell protein (SCP) present an intriguing route for rapid protein production. The oleaginous bacterium Rhodococcus opacus serves as a model organism for understanding microbial lipid production. SCP production has not been explored using an organism from this genus. In the present research, R. opacus strains DSM 1069 and PD630 were fed three agro-waste streams: (1) orange pulp, juice, and peel; (2) lemon pulp, juice, and peel; and (3) corn stover effluent, to determine if these low-cost substrates would be suitable for producing a value-added product, SCP for aquafarming or livestock feed. Both strains used agro-waste carbon sources as a growth substrate to produce protein-rich cell biomass suggesting that that R. opacus can be used to produce SCP using agro-wastes as low-cost substrates.